Clinical Characteristics and Prevalence of Comorbidities according to Metformin Use in Korean Patients with Type 2 Diabetes. (24th July 2020) - Chin, Sang Ouk; Ha, In Gyoon; Rhee, Sang Youl; Jeong, Su Jin; Chon, Suk; Kim, Sung Hoon; Ahn, Kyu Jeung; Baik, Sei Hyun; Park, Yongsoo; Nam, Moon Suk; Lee, Kwan Woo; Woo, Jeong Taek
Abstract : Background/Aims. This study was designed to identify the clinical characteristics of Korean patients with type 2 diabetes according to metformin use. Methods . This cross-sectional study based on the Korean National Diabetes Program 2 registry used its baseline clinical data collected from seven participating university hospitals in Korea. Patients with no significant changes in their oral hypoglycemic agents and no diabetes-related complications within the year prior to participation were enrolled. Patients' clinical characteristics according to metformin use were analyzed. Results . Among 858 subjects included in the analyses, 706 were metformin users and 152 were nonmetformin users. Metformin users were significantly younger and had higher and glycated hemoglobin with significantly lower rates of accompanying microvascular complications such as retinopathy, cataracts, overt proteinuria, renal insufficiency, and peripheral neuropathy than nonusers. Meanwhile, there was a significantly lower prevalence of malignancy and depression among metformin users. These associations remained significant in multivariate analyses. The prevalence rate of macrovascular complications was not significantly different between the two groups. Conclusions . There were significant differences with respect to clinical characteristics and comorbidity prevalence according to metformin use among Korean type 2 diabetes patients. Long-term follow-up of these patients is necessary to observe how this difference will affect clinical outcomes for these patients.